On Intuitionistic Fuzzy Soft Groups - Faruk Karaaslan; Kenan Kaygisiz; Naim Çağman (Journal of New Results in Science)
–In this paper, we give some basic properties ofintuitionistic fuzzy soft sets and (α, β)-level sets. Also we defineimage of an intuitionistic fuzzy soft set under a function, productof two intuitionistic fuzzy soft sets and obtain some results. Inaddition, we define intuitionistic fuzzy soft group and investigatetheir properties